2009
DOI: 10.3945/jn.108.099184
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Dietary Vitamin B-6 Restriction Raises Plasma Glycine and Cystathionine Concentrations While Minimally Affecting the Rates of Glycine Turnover and Glycine Cleavage in Healthy Men and Women

Abstract: Glycine is a precursor of purines, protein, glutathione, and 1-carbon units as 5,10-methylenetetrahydrofolate. Glycine decarboxylation through the glycine cleavage system (GCS) and glycine-serine transformation by serine hydroxymethyltransferase (SHMT) require pyridoxal 5'-phosphate (PLP; active form of vitamin B-6) as a coenzyme. The intake of vitamin B-6 is frequently low in humans. Therefore, we determined the effects of vitamin B-6 restriction on whole-body glycine flux, the rate of glycine decarboxylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(104 citation statements)
references
References 52 publications
9
89
6
Order By: Relevance
“…We did not detect the enrichment of either glycolate or oxalate with a single labeled carbon, indicating that the metabolism did not involve the splitting of the carbon-carbon bond. Whole body flux values were calculated for each of the glycine infusion levels (Table 2) and were similar to those previously reported [23][24][25][26][27]. Our results suggest that glycine metabolism increased at the higher infusion rate when plasma glycine levels were increased, as the flux was 72% higher (P = 0.02).…”
Section: Infusion With [12-13 C 2 ] Glycine At 60 µMoles/kg/hrsupporting
confidence: 70%
“…We did not detect the enrichment of either glycolate or oxalate with a single labeled carbon, indicating that the metabolism did not involve the splitting of the carbon-carbon bond. Whole body flux values were calculated for each of the glycine infusion levels (Table 2) and were similar to those previously reported [23][24][25][26][27]. Our results suggest that glycine metabolism increased at the higher infusion rate when plasma glycine levels were increased, as the flux was 72% higher (P = 0.02).…”
Section: Infusion With [12-13 C 2 ] Glycine At 60 µMoles/kg/hrsupporting
confidence: 70%
“…However, metabolic changes develop even when plasma PLP is between 20 and 30 nM. As reported in our previous studies, plasma amino acid profiles were altered with elevation of cystathionine and glycine in healthy participants when their plasma PLP is between 20 and 30 nM, which is viewed as a marginal deficiency (12,24). Population-based observational studies show mean concentrations of plasma PLP in healthy people in the range of 50 nM (18,41).…”
mentioning
confidence: 81%
“…One group of cells was cultured in the standard formulation of MEM/EBSS medium containing a nonphysiologically high concentration of pyridoxal (PL, 2,000 nM). Three groups of cells were concurrently cultured in vitamin B-6-free media containing lower concentrations of added PL hydrochloride: 10 nM PL corresponding to vitamin B-6 deficiency (23), 20 nM PL representing marginal vitamin B-6 deficiency (12,24), and 50 nM PL representing adequate vitamin B-6 status as reflected by the range of plasma PLP concentration in humans (18,41).…”
Section: Methodsmentioning
confidence: 99%
“…42 Moreover, vitamin B6 restriction has been demonstrated to lead to an increase of plasma glycine concentration. 37 In addition, in a cross-sectional study, plasma concentrations of glycine and serine were lower in individuals with metabolic syndrome compared to those without. 43 We observed that betaine, DMG, sarcosine and glycine concentrations were significantly lower among men with a high BMI.…”
Section: Amino Acid Profiles In Prostate Cancermentioning
confidence: 99%
“…Reduced activity of the glycine cleavage system, as would occur during vitamin B6 deficiency, causes accumulation of glycine. 37 In this way, plasma glycine is a functional biomarker of vitamin B6 status. The glycine cleavage system is a major contributor to cellular 5,10-methylene THF, which is needed for thymidylate synthesis.…”
Section: One-carbon Balance and Prostate Cancermentioning
confidence: 99%